Оптимізація параметрів нового конструктивного елементу з метою підвищення стійкості меблевих тканин до тертя - Сорокіна, С. В.; Акмен, В. О.; Афанасьєва, В. А. (НТУ "ХПІ", 2014)
У зв’язку з наявністю проблеми швидкого зношування мякого елементу диванів протягом сну, запропоновано параметри нового конструктивного элемента з метою зменшення навантаження тертя на тканеве покриття. Шляхом математичного комп'ютерного моделювання, за допомогою методу кореляційно-регресивного аналізу проведено оптимізацію параметрів розміру та маси конструктивного елементу та обрано найбільш оптимальне значення ваги нового елементу, яка складає 4,7 кг при щільності використаного матеріалу– 252 кг/м3 та розмірах 55*241*18 см. Іл.: 5. Бібліогр.: 3. назв.

Because, in spite of modern developments, there is the problem of rapid wear and tear of upholstery fabrics, especially during the frequent operation of sofas to sleep on, current studies are aimed at reducing the burden of friction during this period. The paper proposed the use of a new structural element for upholstered furniture, namely, sofas, in order to reduce the load friction on the fabric covering. To optimize the size and mass of structural element mathematical computer modeling. The process of building a mathematical model of the problem was carried out in three stages using the methods of correlation and regression analysis to measure the closeness of connections indicators. After analysis of trends between him and comparison with experimental data was selected trend that best approximates the experimental data. In accordance with the obtained data was selected the most efficient weight value of the new element, which is 4.7 kg with the density of the material used - 252 kg/m3 and dimensions 55*241*18 see Shows that when using a material with higher density is a significant increase in the mass of the structural element.
Optimization of parameters of new structural element to increase resistance of upholstery fabrics to abrasion
Keywords: український ринок меблів; моделі диванів; поверхневе покриття; комп'ютерне моделювання; оптимізація параметрів; накидка-оболонка; sofa; furniture fabric; parameter optimization; cloak-shell; resistance to friction